Blue rubber bleb nevus syndrome: report of a case - Tatar, Gonca; Özyılkan, Esin; Telatar, Hasan (The Turkish Journal of Pediatrics, 1993)
A case of blue rubber bleb nevus syndrome (BRBNS) in a 17-year old boy with multiple cutaneous and gastrointestinal hemangiomas is presented. The patient had iron deficiency anemia and pica. In addition, we describe, for the first time, left renal artery, right hepatic artery, and ureteral abnormalities in a patient with BRBNS.
Keywords: blue rubber bleb nevus syndrome; gastrointestinal involvement; vascular abnormalities